Knowledge management to improve project communication and implementation - Koskinen, Kaj U. (2004)
This article highlights knowledge management as a part of project management. First, the article focuses on epistemological assumptions. Cognitive-and autopoietic epistemologies are highlighted with the purpose getting a better understanding of what is knowledge and how it develops. Second, the discussion goes on dealing with tacit-and explicit knowledge and their role in different types of projects. Third, the article illustrates two main knowledge management processes: codification and personalization. It is concluded that many delivery-and investment projects are often projects in which the utilization of explicit knowledge and codification type of knowledge management process play a significant role. It is also concluded that many research and development projects are enterprises in which tacit knowledge usage is abundant and personalization type of knowledge management process is a necessity. Fourth, the main content of his article - a division of knowledge-related project management environments into four different entities - is introduced. With the help of this division the project management can understand what type of knowledge management process is needed in different project management contexts. - Reproduced.
Keywords: Project management; Knowledge management